Urgensi Perlindungan Hukum Bagi Pekerja Migran Indonesia dalam Mengantisipasi Konflik Antar Negara - Ahmad Rayhan; Nuryati solapari; Ridwandani Azril (Publication of the International Journal and Academic Research, 2025)
Indonesian Migrant Workers (PMI) are Indonesian citizens who will, are or have done Work by Receiving Wages outside the Territory of Indonesia, this is regulated in Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers and its derivative Regulations. Indonesian Migrant Workers are Indonesian citizens who are still under the authority of the Indonesian government, however the position of Indonesian Migrant Workers abroad is very vulnerable to facing unpleasant cases such as Violence, Human Trafficking, Illegal Migrant Workers and various other cases. These cases trigger conflicts between Indonesia and the recipient countries of Indonesian Migrant Workers, due to the relationship between 2 different citizenships. So it is important for the Government of the Republic of Indonesia to provide legal protection efforts and Preventive Actions to Indonesian Migrant Workers who will go Abroad, both in terms of administration, readiness and the purpose of Indonesian Migrant Workers. The method used is the Normative Juridical Method, and the purpose of this study is to analyze how the Urgency of Legal Protection for Indonesian Migrant Workers in Anticipating Conflicts Between Countries. The results of this study explain that the role of the government in making regulations or international agreements with countries where Indonesian migrant workers work is very important in order to protect Indonesian citizens and prevent conflicts between countries that can occur due to problems caused by Indonesian migrant workers.